A Ras activation pathway dependent on Syk phosphorylation of protein kinase C - Kawakami, Yuko (National Academy of Sciences, 2003)
Protein kinase C (PKC) and Syk protein tyrosine kinase play critical roles in immune cell activation including that through the high-affinity IgE receptor, FcεRI. Mechanisms by which PKC activation leads to the activation of Ras, a family of GTPases essential for immune cell activation, have been elusive. We present evidence that Tyr-662 and Tyr-658 of PKCβI and PKCα, respectively, are phosphorylated by Syk in the membrane compartment of FcεRI-stimulated mast cells. These phosphorylations require prior PKC autophosphorylation of the adjacent serine residues (Ser-661 and Ser-657, respectively) and generate a binding site for the SH2 domain of the adaptor protein Grb-2. By recruiting the Grb-2/Sos complex to the plasma membrane, these conventional PKC isoforms contribute to the full activation of the Ras/extracellular signal-regulated kinase signaling pathway in FcεRI-stimulated mast cells.